Detection of maladaptive pain in dogs referred for behavioral complaints: challenges and opportunities - Kwik, Jenthe; De Keuster, Tiny; Bosmans, Tim; Mottet, José (Frontiers in Behavioral Neuroscience, 2025)
IntroductionDiagnosing maladaptive pain in dogs with behavioral complaints is challenging, as clinical signs are often non-specific and may be absent during examination. This paper supports veterinary teams in distinguishing behavioral changes that stem from a behavioral disorder, maladaptive pain, or both.MethodsThe medical records of ten client-owned dogs referred to the authors’ behavioral practice were selected to identify challenges in recognizing maladaptive pain and to highlight diagnostic tools. A Toolbox approach was used for assessment, integrating caregiver questionnaires, medical history, home video analysis, clinical observation, and a timeline. Behavioral signs were categorized as green (adaptive) or red (maladaptive) flags to facilitate differential diagnosis and guide treatment decisions.ResultsAll dogs (n = 10) were diagnosed with altered socioemotional functioning. In 7/10 cases, the Toolbox approach indicated maladaptive pain, confirmed by medical imaging in 3/7 cases. Multimodal treatment led to recovery in 6/7 dogs. In 3/10 dogs with behavioral histories, an acute worsening of signs suggested maladaptive pain, confirmed by imaging in all cases. Treatment led to partial recovery in 2/3 dogs, while one was euthanized due to neoplasia. Diagnostic challenges fell into three categories: bias in observation, clinical examination, and interpretation of behavioral signs.ConclusionDiagnosing maladaptive pain in dogs with behavioral problems requires a comprehensive approach. Recognizing red flags, using targeted diagnostic tools, and implementing multimodal treatment strategies can improve quality of life, reduce suffering, and enhance case management.